Analisis pertukaran udara per jam pada ventilasi laboratorium di kawasan hutan hujan tropis - Namira Yolanda; Erlinda Ratnasari Putri; Rahmawati Munir (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
Kalimantan is an island surrounded by tropical rain forests and has hot and humid weather because it is crossed by the equator. The hot and humid weather affects the human working climate in the exchange of air in the room, for example in the laboratory. This study objective was to know the amount of air exchange per hour at the Samarinda Occupational Safety and Health Center. The tools used were the TESTO 425 anemometer, a digital meter, a lutron-abh 4225, and a laptop. The chambers where air changes per hour measured were the main laboratory, weighing chamber, UV-VIS spectrophotometer chamber, and atomic absorption and chromatography spectrophotometer chamber. Based on the results of measurements and data analysis, it can be concluded that the ventilation system of 3 out of 4 laboratory chambers has met the recommendation. The calculation step was carried out by entering the measured parameters into the ACH equation. The last stage, the analysis was carried out to compare the ACH values based on the ASHRAE recommendations. Based on the results, the average value of ACH for the main laboratory room was 3,8 x/hour, weighing chamber was 15,61 x/hour, UV-VIS spectrophotometer was 12,7 x/hour, and atomic absorption and chromatography spectrophotometer chamber was 12,78 x/hour. The average number of air changes per hour (ACH) at the laboratory is 11,22 x/hour, where the amount of air changes per hour is in accordance with the ASHRAE (2011) recommendation for a good and healthy environment, the ASHRAE recommendations with the ACH of the Laboratory room ranging from 6 to 12 x/hour. It can be concluded that wind speed, cross-sectional area, and room volume affect the amount of air exchange per hour.